Epidemiological Profile of HIV Pregnant Women at the University Hospital Centre for Mother and Child Lagoon (Benin) - LOKOSSOU, Mègnissè Sèna H. S.; OGOUDJOBI, OGOURINDÉ MATHIEU; ABOUBAKAR, MOUFALILOU (My University, 2018)
Objective: Vertical transmission of HIV remains the second mode of infection in Benin. To study the epidemiological aspects of HIV infection during the pregnancy at University Hospital Centre for Mother and Child Lagoon (CHU-MEL). Patients and methods: We conducted a descriptive cross-sectional study at the Mother and Child Hospital in Benin from 1 January 2015 to 30 June 2017. The sampling was exhaustive. The selection criteria were: all pregnant or parturient seropositive who were taken care of during the study period at HOMEL. The data analysis was done with the Epi Info software, by calculating averages and standard deviations. Results and conclusion: The prevalence rate of HIV amongst pregnant women was 1.9% (188/9554). The average age was 30 years old ± 5 years. They were married (45.6%), crafts women (67.7%), lived in a monogamous family (60.3%) and gave birth at least once (73.8%). The prevalence rate varied depending on the level of education; it was lower among the unschooled (17.5%), around (7.4%) among those who went to high school and higher among those with an intermediate level of education. HIV prevalence remains stable in the population of pregnant women. The education of young girls and the increasing purchasing power of women must be taken into consideration when drafting HIV control strategies.
Keywords: Prevalence; Pregnant; HIV; HOMEL